Heterosis and Combining Ability Analysis in Sunflower (Helianthus annuus L.) Using Line × Tester Mating Design for Yield and Oil Improvement - Ahmed, Ishfaq; Ghayas, Muhammad; Shah, Ali; Muhammad, Ghulam; Ghafoor, Abdul; Asghar, Ali (Indus Journal of Bioscience Research, 2025)
This study aimed to assess sunflower genotypes’ heterosis and combining ability using a line × tester mating design to improve key agronomic traits, such as yield per plant, oil content, and 1000 achene weight. Four sunflower lines (A-27, A-28, A-29, and A-30) and three testers (A-41, A-42, and A-43) were used to create hybrids. The experimental design was laid out in a Randomized Complete Block Design (RCBD) with three replications, and the data were analyzed for general combining ability (GCA) and specific combining ability (SCA) effects. The results revealed that the hybrids significantly outperformed the parental lines in all major traits, with yield per plant and oil content showing the greatest improvements. The GCA effects were significant for yield and oil content, suggesting that additive genetic effects were important in inheriting these traits. The SCA effects indicated that non-additive genetic effects also substantially influenced hybrid performance, particularly for yield per plant. This study identified several superior hybrids with enhanced yield potential and oil content suitable for commercial cultivation in Pakistan’s agro-climatic conditions. his study highlights the potential of hybrid sunflower breeding to enhance key agronomic traits such as yield, oil content, and achene weight. The Line Tester mating design confirmed the importance of both additive and non-additive genetic influences. Hybrids outperformed parental lines, emphasizing the need for locally adapted varieties. However, limitations include a small sample size and lack of multi-location trials. Future research should integrate molecular techniques and focus on disease resistance and drought tolerance for improved hybrid performance and sustainability.